On a minimum set of equations for parameterisations in comprehensive ocean circulation models. (December 2021) - Shevchenko, I.; Berloff, P.
Abstract: The complexity of comprehensive ocean models poses an important question for parameterisations: is there a minimum set of equations that should be parameterised, on the one hand, to reduce the development to a minimum, and, on the other hand, to ensure an accurate representation of large-scale flow patterns? This work seeks to answer the question to assist modern parameterisations be more selective in their targets. For this, we considered a model of the North Atlantic and studied contributions of different model equations to the accuracy of representation of the Gulf Stream at low resolution. Our results suggest that one should focus on parameterising the tracer equations for temperature and salinity, and may leave the other equations in the hydrodynamic part, as well as the atmospheric model unmodified. They also suggest that parameterisations representing only Kinetic Energy Backscatter cannot be fully efficient and the main focus should be shifted towards developing parameterisations of combined Potential/Kinetic Energy Backscatters. Highlights: We search for a minimum set of equations needed to parameterise the Gulf Stream (GS). Augmentation of only the tracer equations is enough to preserve the modelled GS. Augmentation mainly injects potential energy. It may be sufficient to parameterise only the thermodynamic tracer equations.